An Empirical study into the determinants of corporate social disclosure among malaysian public-listed companies - Yee, Christine Wei Mun (2004)
In today’s society, businesses are not just simply the vehicles for generating value to shareholders alone. From the wider stakeholder perspective, they are also expected to do this in a socially responsible manner, thus the rise of corporate social responsibility (CSR) concept. As the fulcrum of businesses move from shareholders to stakeholders, financial information alone no longer suffices. With this growing need for broader accountability,the need for reporting on CSR activities is also amplified. In the case of Malaysia, a newly industrialised country moving towards a knowledge economy, human resources form an important component in this vision. As such, this study intends to identify the characteristics of companies that exhibit CSR commitment related to human resources (HR) , which will help policy-makers formulate effective policies to raise the level of such CSR. Using stakeholder theory, political economy theory and legitimacy theory as its platform, this study hypothesised that size, profitability, foreign ownership, sector and age are associated to a company’s HR-related CSR. The 2003 annual reports of the 100 component companies of the Kuala Lumpur Composite Index (KLCI) were used for this research. Based on a framework that was developed for assessing HR-related disclosures, content analysis was carried out on these annual reports and CSR disclosures (CSD) quantified by dichotomous scoring on 7 categories. A score of 0 was given for non-disclosure and 1 was given for disclosure. It was found that the highest CSD score was 6 – no company had provided disclosure on all 7 categories. Statistical tests comprising of t-tests, ANOVA (analysis of variance) tests and Pearson’s Correlation were carried out to determine the association between HR-related CSD scores and the selected company-level characteristics. Results of these tests found that the company-level characteristics that are associated positively with CSD are size and profitability, while companies in the 10-20 year age group exhibited higher CSD. The principal findings from this study are in line with stakeholder theory and political economy theory. These suggest that companies provide CSD as a method of protecting their self-interests in the face of social and political pressures. It is thus more extensively carried out by those with wider stakeholder base, higher agency costs, political costs and social prominence. Affordability in terms of resources is a realistic constraining factor, as it was seen that highly profitable companies provided more CSD. In terms of legitimacy,although the findings based on listing age and company size support this theory, the findings regarding profitability provided mixed signals – those companies with low profits, or even losses, do not appear to provide higher CSD than those of medium profitability.The findings of this study also provide practical applications in that it provides a point of reference for both policy-makers and managers.